초보 · 상급초보간호사의 무형식학습, 공유리더십과 조직사회화의 관계에서 자기효능감의 매개효과 - 김남이(Kim, Nam Yi); 우정희(Woo, Chung Hee) (Kanho Haengjŏng Hakhoe chi = The journal of Korean Nursing Administration Academic Society, 2018)
본 연구는 초보 및 상급초보간호사에서 무형식학습, 공유리더십과 조직사회화의 관계에서 자기효능감의 매개효과를 파악하기 위하여 시도되었다. 조직사회화, 무형식 학습, 공유리더십과 자기효능감을 측정하기 위해 자기보고식의 구조화된 설문지를 이용하였다. 대상은 500병상 이상 규모의 병원에서 근무하는 초보·상급초보간호사이며 자료는 2017년 2월 1일부터 28일까지 수집되었다. 최종분석대상인 136부를 SPSS/WIN 22.0을 이용하여 위계적 회귀분석을 실시하였다. 대상자의 조직사회화에 있어 무형식학습, 공유리더십 및 자기효능감은 통계적으로 유의한 양의 상관성을 나타내었다. 자기효능감은 무형식학습과 공유리더십에 대하여 통계적으로 유의한 양의 상관성을 보여주었다. 또한 자기효능감은 무형식학습 및 공유리더십과 조직사회화 사이에서 부분 매개효과가 있는 것으로 나타났다. 결론적으로 무형식학습과 공유리더십이 높은 조직문화는 낮은 경력의 간호사의 조직사회화에 있어 중요한 요인인 것으로 여겨진다. 자기효능감 또한 그들의 조직사회화를 촉진할 것으로 기대된다. Purpose: The study was done to investigate the mediating effect of self-efficacy on the relationships between informal learning and organizational socialization and between shared leadership and organizational socialization among low career nurses. Methods: A structured self-report questionnaire was used to measure organizational socialization, informal learning, shared leadership and self-efficacy. During February, 2017, data were collected from 136 nurses working in hospitals of more than 500 beds. Data were analyzed using hierarchial multiple linear regression with the SPSS/WIN 22.0 program. Results: Informal learning, shared leadership and self-efficacy were positively correlated with organizational socialization of participants and self-efficacy was positively correlated with informal learning and shared leadership of participants. Also, self-efficacy had a partial mediating effect on the relationship between informal learning, shared leadership and organizational socialization. Conclusion: The findings indicate that organizational culture with high level of informal learning and shared leadership is an important factor for organizational socialization of low career nurses. It is also expected that self-efficacy can further promote their organizational socialization. KCI Citation Count: 3